Use of everyday materials in retrospective nuclear accident dosimetry - Stamoulis, K.; Ioannides, K. G.; Bakola, H.; Papachristodoulou, C. A.; Tsodoulos, L. M. (HNPS Advances in Nuclear Physics, 2019)
Following a large-scale nuclear event, a quantitative estimate of the radiation dose to the general population necessitates the availability of adequate procedures for the assessment of doses. The main objectives of dose reconstruction, namely retrospective dosimetry can be synoptically stated as in the following: a) To guide the provision of proper protection for the population that had been exposed to radiation, b) To provide assuring information to the worrying public and c) To provide input data for epidemiological studies. Amongst the methods used for dose estimation are the Thermoluminescence (TL) and the Optically Stimulated Luminescence (OSL). Methods based on TL and OSL have the advantage that they allow the measurement of the integrated absorbed dose. When the irradiation comes from external sources, materials found within the perimeter of the accident area such as bricks, tiles and pottery and certain household chemicals, can be used. The absorbed dose may be evaluated many years after the accident.